LAM 2018 Monitoring Summary -CSA Adoption and perceived effects. - Bonilla Findji, Osana; Eitzinger, Anton; Andrieu, Nadine; Bejarano, Gustavo; Aguilar, A.; Ortega, Luis A.; Paz, Liliana Patricia; Suchini, JG (2019)
This progress report summarizes the key results from the CSV monitoring undertaken in 2018. It focuses on the levels of CSA implementation in the 4 LAM Climate-Smart villages (Colombia, Guatemala, Honduras and Nicaragua) and gender-disaggregated perceived effects of CSA practices on households livelihoods and gender dimensions